2008
DOI: 10.1002/ajh.21254
|View full text |Cite
|
Sign up to set email alerts
|

Ankyrin‐linked hereditary spherocytosis in an African–American kindred

Abstract: Mutations of ankyrin-1 are the most frequent cause of the inherited hemolytic anemia, hereditary spherocytosis (HS), in people of European ancestry. Ankyrin-1, which provides the primary linkage between the erythrocyte membrane skeleton and the plasma membrane, has numerous isoforms generated by alternative splicing, alternate polyadenylation, use of tissue-specific promoters, and alternate NH 2 or COOH-termini. Mutation detection in erythrocyte membrane protein genes, including ankyrin, has been a challenge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…[1][2][3][4][5] Numerous mutations in the genes encoding these membrane proteins have been described. Destruction of poorly deformable HS erythrocytes in the spleen is the primary cause of hemolysis in patients with HS.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Numerous mutations in the genes encoding these membrane proteins have been described. Destruction of poorly deformable HS erythrocytes in the spleen is the primary cause of hemolysis in patients with HS.…”
Section: Pathogenesismentioning
confidence: 99%
“…[1][2][3][4][5] HS occurs worldwide and affects individuals from all racial and ethnic groups. Individual pediatricians encounter HS uncommonly, but hospitals and health care systems with large delivery services regularly deal with this condition, particularly in white neonates of northern European ancestry, in whom the condition can be as frequent as 1 in 1000 to 2000 births.…”
mentioning
confidence: 99%
“…However, as the result of extreme allelic heterogeneity of HS-causing genes, many alleles do not reach sufficient frequencies [55] or achieve consistent symptoms [56] to be easily associated with malaria protection. In addition, technical difficulties [29], confounding factors from large genetic variation in African populations [57], as well as poor diagnostics and health systems [57], pose significant challenges for dissecting the connection between HS and malaria. Furthermore, the varying allele frequency in African populations might introduce epistasis effects, possibly masking the genotype-phenotype associated typically observed in other populations [58].…”
Section: Discussionmentioning
confidence: 99%
“…HS is caused by mutations in ankyrin, spectrins, band 3 and protein 4.2, with ankyrin mutations contributing to more than 50% of all HS cases [23-27], where the severity depends greatly on the location and the nature of mutations [28]. However, the prevalence of HS in malaria endemic regions is not well studied; only isolated cases were reported [29-32]. Nevertheless, in vivo and in vitro studies have repeatedly suggested an association of HS with increased malaria resistance, and several mechanisms have been proposed, although not all of them were consistent [33-36].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, ankyrin gene mutations are not only unique to individual kindreds but are also located throughout the coding exons and promoter region of the ankyrin gene. 5 To date, a total of 61 mutations are included in the HGMD public database. Small deletions and missense/nonsense mutations have been identified in approximately 70% of all mutations in the ANK1 gene.…”
mentioning
confidence: 99%